Former dynamic behaviour of a cold-based valley glacier on Svalbard revealed by basal ice and structural glaciology investigations - Lovell, H.; Fleming, E.J.; Benn, D.I.; Hubbard, B.; Lukas, S.; Naegeli, K. (Journal of Glaciology, 2015)
H.L. was funded by a UK Natural Environment Research Council (NERC) PhD studentship (NE/I528050/1), the Queen Mary Postgraduate Research Fund, and an Arctic Field Grant from the Research Council of Norway. E.J.F. was funded by a NERC PhD studentship as part of the GAINS (Glacial Activity in Neoproterozoic Svalbard) grant (NE/H004963/1). K.N. was funded by an Arctic Field Grant, the Swiss Society for Speleology, and the travel grant commission of the Swiss Academy of Science. Large numbers of small valley glaciers on Svalbard were thicker and more extensive during the Little Ice Age (LIA), demonstrated by prominent ice-cored moraines up to several kilometres beyond present-day margins. The majority of these glaciers have since experienced a long period of strongly negative mass balance during the 20th century and are now largely frozen to their beds, indicating they are likely to have undergone a thermal transition from a polythermal to a cold-based regime. We present evidence for such a switch by reconstructing the former flow dynamics and thermal regime of Tellbreen, a small cold-based valley glacier in central Spitsbergen, based on its basal sequence and glaciological structures. Within the basal sequence, the underlying matrix-supported diamict is interpreted as saturated subglacial traction till which has frozen at the bed, indicating that the thermal switch has resulted in a cessation of subglacial sediment deformation due to freezing of the former deforming layer. This is overlain by debris-poor dispersed facies ice, interpreted to have formed through strain-induced metamorphism of englacial ice. The sequential development of structures includes arcuate fracture traces, interpreted as shear planes formed in a compressive/transpressive stress regime; and fracture traces, interpreted as healed extensional crevasses. The formation of these sediment/ice facies and structures is indicative of dynamic, warm-based flow, most likely during the LIA when the glacier was significantly thicker. Peer reviewed